Tree species composition of 0.1 ha plot at UiTM Jengka education forest (line 13) - Abdul Rahim, Nur Farah Dayana; Zakariya, Norhidayu; Ismail, Nor Izati; Muhammad, Muhd Nasharuddin; Abdul Halim, Mohd Hariz Hifzuddin (2012)
Research carried out is to identify the species composition and density of trees in 0.1 ha plots of forest education in UiTM Jengka. Research is based on tree species with diameter measuring more than 5 cm in accordance with the breast height and 1.3 m from ground level. Plot are established in the study site are located in line 13 at UiTM Jengka Education Forest. In addition, this research involves 153 trees in a plot area measuring 50m x 20m wide. This number of tree also was represents 63 genera of 88 species from 30 families. The tree density are illustrates the number of individuals per unit area or unit volume. The result show that most species found in our plot are from families Dipterocarpecea, Euphorbiacea and Myrtacea. For the abundance density, calculation showed that the density for trees with diameter at breast height of 5 cm and above at the study area were 153 individuals or 1530 individuals per ha.